Quality Control And Dosimetric Accuracy Assessment Of Cobalt-60 Teletherapy Unit At Ssdl, Bangladesh (Bangladesh Journal of Physics, 2025)
External beam radiotherapy, often known as teletherapy, is one of the most efficient ways to treat cancer since it targets harmful cells with radiation. Dosimetric accuracy of a recently installed Cobalt-60 teletherapy unit (Theratron Equinox100#2149, Initial Activity: 12000 Ci) at the Bangladesh Atomic Energy Commission's Secondary Standard Dosimetry Laboratory (SSDL), Savar, Dhaka, has been the main focus of this work. Several measurements are made that are necessary to ensure the accuracy of the Cobalt-60 teletherapy unit in terms of dosimetric level, specifically the accuracy of absolute and relative dosimetry. These measurements include the following dosimetric parameters: absorbed dose to water, percentage depth dose (PDD), beam profile, inter-chamber comparison (to ensure the highest level of dosimetry accuracy), and comparison of absorbed doses using two protocols named IAEA TRS-277 and IAEA TRS-398. The absorbed dose rate at reference field size (10 × 10 cm2) was found to be 1.548 Gy/min with an uncertainty of ±0.020. In the case of the inter-chamber comparison, the maximum deviation among values of absorbed dose to water for four Farmer chambers was 0.27% for Dw(Zref) and 0.26% for Dw(Zmax). The resultant output of this study may contribute to developing the treatment planning system in the realm of cancer treatment.Bangladesh Journal of Physics, 28(1), 1-10, June 2021